Forestry features of regionalization of forest reproductive material - Oleg Danchuk; Vasyl Blystiv; Zinovii Yurkiv; Vitaly Vovchanskyi (Наукові праці Лісівничої академії наук України)
The theoretical basis for the development of methodological foundations for improving forest seed zoning in Ukraine is the natural intraspecific variability of tree species, which was formed in the process of evolution under the influence of mutations, recombinations and natural selection as a result of the adaptation of local populations to the conditions of their functioning.